SINGLE WHOLE-LEG COMPRESSION ULTRASOUND FOR EXCLUSION OF DEEP VEIN THROMBOSIS IN SYMPTOMATIC AMBULATORY PATIENTS: A PROSPECTIVE OBSERVATIONAL COHORT STUDY. Issue 10 (7th September 2013) - Horner, D; Hogg, K; Body, R; Mackway-Jones, K
Abstract : Objectives & Background: International guidance has recently recommended serial proximal compression ultrasound (CUS) as first line imaging for suspected deep vein thrombosis (DVT). Limitations with this strategy include attrition, lack of a clear diagnosis, and increased costs associated with serial resource use / clinical review. Single whole-leg CUS is a routine alternative diagnostic strategy that can reduce repeat attendance and identify alternative pathology. We sought to assess the performance characteristics of an established emergency department ambulatory protocol incorporating whole-leg CUS by non-physicians for exclusion of DVT. Methods: A prospective observational cohort study, conducted between July 2011 and April 2012. Consecutive, ambulatory, adult patients with suspected DVT and negative or inconclusive whole-leg CUS had anticoagulation initially withheld and were followed up after three months. The primary outcome was a predefined clinically relevant adverse event rate: a subsequent diagnosis of symptomatic venous thromboembolism (VTE) or VTE related death during three month follow up. Secondary outcomes included alternative diagnoses, technical failure rate and characteristics associated with failure. Results: 212 patients agreed to participate and were followed for three months. One patient was subsequently diagnosed with an isolated distal DVT. The adverse event rate was thus 1/212, 0.47% (95% confidence interval 0.08 to 2.62%). 150/212 patients were provided with a clear documented alternative diagnosis. CUS directly contributed to or confirmed the alternate diagnosis in 55/150 patients. Technical imaging failure occurred in 11.3% of suspected cases (95% CI 7.7 to 16.3). Several potential predictors of an inconclusive result were identified on multivariate analysis, including obesity, active infection, immobilisation and active cancer. Conclusion: Patients who have anticoagulation withheld following a negative or inconclusive whole leg CUS for suspected DVT have a low rate of adverse events at 3 months. Including the calf in ultrasound examination aided and clarified diagnosis in approximately one third of patients. Technical failure remains an issue: several factors were significantly associated with inconclusive results in our cohort and may warrant an alternative diagnostic approachAbstract 008 Table 2